2018
DOI: 10.1111/ecc.12870
|View full text |Cite
|
Sign up to set email alerts
|

Discussing potential recurrence after lung cancer surgery: Uncertainties and challenges

Abstract: Patients with lung cancer who undergo surgery may potentially be cured. The resulting pathological staging gives an indication of 5-year survival and whether further treatment is recommended. To date, there is little research evidence regarding the way potential recurrence is communicated to patients by staff. This qualitative research used case studies to explore how information disclosure about possible recurrence was managed following lung cancer surgery and aimed to identify practice implications for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…So how can we understand why the restitution narrative of ‘being lucky’ dominates? As mentioned in the introduction, a study by Johnson et al (2018) found that surgeons wanted to boost patients' hopes with an optimistic message, even when the prognosis was rather poor. The desire to induce hope and downplay illness and treatment is similarly found in the present study when the surgeon call surgery ‘a quiet day at the office’ and adjuvant chemotherapy is deemphasised by calling information at the outpatient clinic ‘good news’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So how can we understand why the restitution narrative of ‘being lucky’ dominates? As mentioned in the introduction, a study by Johnson et al (2018) found that surgeons wanted to boost patients' hopes with an optimistic message, even when the prognosis was rather poor. The desire to induce hope and downplay illness and treatment is similarly found in the present study when the surgeon call surgery ‘a quiet day at the office’ and adjuvant chemotherapy is deemphasised by calling information at the outpatient clinic ‘good news’.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research exploring how patients with lung cancer and clinicians engage in dialogue about illness and treatment. One study by Johnson et al (2018) found that lung cancer is described in positive terms with an emphasis on hope; surgeons found it essential to deliver information in an optimistic way, even when the information was not particularly good. There is a paradox in the experiences described by lung cancer patients, where a high prevalence of emotional distress and physical and psychosocial challenges contrasts with an unmet need for support from clinicians, who tend to present the disease in a positive light.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has a high incidence and mortality[ 11 , 12 ], and the current clinical treatment for patients with lung cancer is surgery[ 13 , 14 ]; even after surgery, patients are prone to recurrence[ 15 ]; therefore, more patients need to be treated with adjuvant chemotherapy to reduce the risk of disease recurrence and ensure the effectiveness of treatment[ 16 ]. However, due to the fear of disease and surgery and the side effects of chemotherapy, patients are prone to self-abdication, and therefore, they receive insufficient treatment[ 17 ], which affects their overall outcome[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dominant illness narratives seem to have an effect on how emotional reactions can be expressed and thereby the possibility for ill people to be heard and recognised in their suffering. Furthermore, research indicates an under-recognition of lung cancer patients' worries and concerns in the clinical encounter with healthcare professionals [9,[22][23][24]. In addition, lung cancer is seen as an individual responsibility because of the association between the disease and smoking, implying emotions of stigma, shame and blame [25].…”
Section: Introductionmentioning
confidence: 99%